Approach to SARS-CoV-2 Vaccination in Patients With Multiple Sclerosis - Woopen, Christina; Schleußner, Katharina; Akgün, Katja; Ziemssen, Tjalf (Frontiers in Immunology, 2021)
For more than a year now, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been causing the coronavirus disease (COVID-19) pandemic with high mortality and detrimental effects on society, economy, and individual lives. Great hopes are being placed on vaccination as one of the most potent escape strategies from the pandemic and multiple vaccines are already in clinical use. However, there is still a lot of insecurity about the safety and efficacy of vaccines in patients with autoimmune diseases like multiple sclerosis (MS), especially under treatment with immunomodulatory or immunosuppressive drugs. We propose strategic approaches to SARS-CoV-2 vaccination management in MS patients and encourage fellow physicians to measure the immune response in their patients. Notably, both humoral and cellular responses should be considered since the immunological equivalent for protection from SARS-CoV-2 after infection or vaccination still remains undefined and will most likely involve antiviral cellular immunity. It is important to gain insights into the vaccine response of immunocompromised patients in order to be able to deduce sensible strategies for vaccination in the future.